ISTIHSAN: DALIL SYARA` YANG DIPERSELISIHKAN - Noorwahidah, Noorwahidah (Universitas Islam Negeri Antasari Banjarmasin, 2016)
Autenticity of istihsan as syara` argument disputed by scholars. Group of Hanafiyah, Malikiyah, and most Hanabilah scholars use istihsan as an argument, but Syafi`iyah, Zhahiriyah, Mu'tazili, and Shi'a scholars reject istihsan. The dispute happened because the difference of interpreting of istihsan. The scholars who use as argument interpret istihsan as turned away from will of qiyas to more powerful qiyas or specialized qiyas because there is stronger evidence thereof, meanwhile, scholars who refuse define istihsan as all things considered good by the mujtahid by his wits. Substantively all scholars, both who use and who reject istihsan using it in some law conclusion, although scholars who reject not call it as an istihsan. They categorize it as a qiyas.